1990
DOI: 10.1300/j272v01n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sexual abuse among boys in treatment for chemical dependency

Abstract: Chemical dependency in adolescence is compounded frequently by environmental and developmental difficulties. Victims of child sexual abuse are believed to be at increased risk of psychological and behavioral problems, including alcohol and drug abuse. However, empirically derived evidence of correlates of sexual abuse victimization among boys is scarce. In a sample of 1,227 boys in adolescent chemical dependency treatment centers, only a small proportion (6.6%) disclosed a history of intrafamilial or extrafami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the original study, physical abuse was shown to be the most contributory in discriminating adolescent drug users from non-drug users. Harrison, Edwall, Hoffman, and Worthen (1990) also found that in their group of chemically dependent adolescent males, many of them indicated a history of family violence.…”
Section: Journal Of Child and Adolescent Substance Abuse 72mentioning
confidence: 94%
“…In the original study, physical abuse was shown to be the most contributory in discriminating adolescent drug users from non-drug users. Harrison, Edwall, Hoffman, and Worthen (1990) also found that in their group of chemically dependent adolescent males, many of them indicated a history of family violence.…”
Section: Journal Of Child and Adolescent Substance Abuse 72mentioning
confidence: 94%
“…Several studies have demonstrated that youth who have a history of physical and/or sexual abuse are at increased risk of depressive disorders, conduct disorder, and alcohol, tobacco, and drug use (Dembo et al, 1988;Harrison, Edwall, Hoffman, & Worthen, 1990;Harrison & Hoffman, 1989;Kaplan et al, 1998). Physical and sexual abuse have been related to illicit drug use among diverse groups of adolescents, including juvenile detainees (Dembo et al, 1988), high school students (Harrison, Fulkerson, & Beebe, 1997), and psychiatric inpatients (Hussey & Singer, 1993;Singer, Petchers, & Hussey, 1989).…”
mentioning
confidence: 99%
“…Substanceabusing youth in treatment, who have a history of sexual abuse, have also been shown to have higher rates of arrests and interactions with the criminal justice system, compared with nonabused youth (Harrison & Hoffman, 1989). Moreover, although rates of sexual abuse are typically higher among substance-abusing girls than boys (Rounds-Bryant, Kristiansen, Fairbank, & Hubbard, 1998), sexual abuse among boys appears to be common, underreported, and undertreated, as well as strongly associated with substance use problems (Holmes & Slap, 1998;Rohsenow, Corbett, & Devine, 1988;Harrison et al 1990).…”
mentioning
confidence: 99%
“…Among males, those with a history of sexual abuse used significantly more tobacco and marijuana compared with those who were not abused (Chandy et al, 1997). Other studies found that victims of sexual abuse were also more likely to drink daily, regularly use stimulants (Harrison et al, 1990), be a current smoker (De Von Figueroa-Moseley, Landrine, & Klonoff, 2004), and report dependence on alcohol, marijuana, and "hard drugs" (Kilpatrick et al, 2000). Victims of sexual abuse also begin substance use at an earlier age than those who are not victims (De Von FigueroaMoseley et al, 2004;Kilpatrick et al, 2000).…”
Section: Sexual Abuse and Substance Usementioning
confidence: 98%
“…Studies on males have shown similar effects. For example, Chandy, Blum, and Resnick (1997) and Harrison, Edwall, Hoffman, and Worthen (1990) found that American males with a history of sexual abuse were significantly more likely to have ever attempted suicide or had thoughts about suicide than those with no history of sexual abuse. Among sexually abused males, the duration of the abuse, use of force during the abuse, and high conformity to masculine norms increased the likelihood of a suicide attempt.…”
Section: Sexual Abuse and Suicidementioning
confidence: 99%